A retórica no julgamento de Eldorado dos Carajás: um estudo do Tribunal do Júri como ritual - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2002)
The jury court is considered one of the only democratic institutions in our legal system. In it, the defendant is judged by his peers. However, the use of this institution has been reduced over time. Today it is only used, in Brazil, for the trials of intentional crimes against life. As is the case of Eldorado dos Carajás. This case was chosen as a base judgment for the variety of social issues presented. The present work is a study of the rhetoric used in this Court for the outcome of the trial: the verdict. In other words, it is an analysis of which arguments are used by the parties and how they influence the verdict, together with the other people involved in the process and public opinion and the media. To this end, the case files (documentation) and interviews with the representatives of the parties involved in the trial have been analyzed so far. By reading the records and drawing a parallel with the theories of the construction of truth in the legal world presented by Kant de Lima and Michel Foucault, we noticed the great political influence on the trial and that many aspects besides the legal one influenced and still influence the progress of the process, such as the corporativism of the police and the pressure exerted by public opinion, especially international public opinion. The same way was observed in the interviews.
The rhetoric in the Eldorado dos Carajás trial: a study of the jury court as ritual
Keywords: Julgamentos; Eldorado dos Carajás; CNPQ::CIENCIAS HUMANAS::ANTROPOLOGIA